Oral adverse effects: drug‐induced tongue disorders. (3rd November 2020) - Aziz, Yalda; Rademacher, Willem Maria Hubertus; Hielema, Atty; Wishaw, Scott Bradley Patton; van Diermen, Denise Edwina; de Lange, Jan; Vissink, Arjan; Rozema, Frederik Reinder
Abstract: Objectives: Due to a worldwide increase in drug consumption, oral healthcare professionals are frequently confronted with patients using one or more drugs. A large number of drugs can be accompanied with adverse drug reactions in the orofacial region, amongst others of the tongue. This paper aims to give an overview of drugs that are known to be accompanied with tongue disorders. Materials and methods: The national drug information database for Dutch pharmacists, composed of scientific drug information, guidelines and summaries of product characteristics, was analysed for drug‐induced tongue disorders. "MedDRA classification" and "Anatomical Therapeutic Chemical codes" were used to categorize the disorders. Results: The database comprises of 1645 drugs of which 121 (7.4%) are documented to be accompanied with tongue disorders as an adverse effect. Drug‐induced tongue disorders are predominantly observed in the following drug categories: "nervous systems, " "anti‐infectives for systemic use" and "alimentary tract and metabolism". The most common drug‐induced tongue disorders are glossitis, tongue oedema, tongue discoloration and burning tongue. Conclusion: Healthcare professionals are frequently confronted with drugs that can cause tongue disorders. The overview of drugs reported in this article supports clinicians in their awareness, diagnosis and treatment of drug‐induced tongue disorders.